Faktor-Faktor yang Mempengaruhi Penyerapan Anggaran: Perencanaan Anggaran, Pengadaan Barang dan Jasa Serta Partisipasi Anggaran - Kuntadi, Cris; Adi Nugroho, Didiet (Jurnal Ilmu Manajemen Terapan, 2023)
Budget absorption as a performance indicator still has problems with low realization and tends to be high at the end of the year. These problems are suspected to be due to the influence of budget planning, procurement of goods and services and budget participation. This article reviews the factors that influence budget absorption, namely: budget planning, procurement of goods and services and budget participation, a literature study on State Financial Management. The purpose of writing this article is to build a hypothesis on the influence between variables to be used in further research. The results of this literature review article are: 1) budget planning affects budget absorption; 2) Procurement of goods and services affects the Absorption of the Budget; and 3) Budget Participation affects Budget Absorption.